An evaluative comparison of lignocellulosic pyrolysis products derived from various parts of Populus deltoides trees and Panicum virgatum grass in an inductively heated reactor. (1st September 2018) - Daniel, Dideolu J.; Ellison, Candice R.; Bursavich, Jacob; Benbow, McKenna; Favrot, Caroline; Blazier, Michael A.; Marculescu, Cosmin; Nokes, Sue E.; Boldor, Dorin
Graphical abstract: Highlights: Inductive-based fast pyrolysis of cottonwood and switchgrass are critically compared. Pyrolysis profiles and kinetics of poplar stem, trunk, branches, and switchgrass. Highest and lowest bio-oil yields from poplar stem and branch respectively. Switchgrass yields maximum bio-oil at lowest pyrolysis temperature (450 °C). Abstract: Poplar is considered a suitable resource for production of renewable fuels and chemicals due to its rapid growth and tolerance to environmental stresses. Switchgrass is also extensively studied for biofuel production due to its use as a resource-efficient low-input plant and ability to grow and thrive in diverse weather or soil conditions. In this study, fast pyrolysis of biomass obtained from various parts (main stem, secondary stems, branches) of eastern cottonwood ( Populus deltoides ) and switchgrass ( Panicum virgatum) was carried out in an inductively heated reactor. Devolatilization rates (ranging from 450 °C to 600 °C) were initially obtained to determine their decomposition kinetics and estimate process parameters (temperatures and times) suitable for their pyrolysis using this method of pyrolysis. The effect of temperature (450 °C, 500 °C, 550 °C) on pyrolysis product yields and composition was investigated. Results indicate that activation energies ranged from 9.2 to 13.5 kJ/mol, while pre-exponential constants ranged from 0.23 to 0.51 s −1 . The maximum quantity of bio-oil of 39.8% ± 9.50 was obtained from poplar stem at 450 °C whereas the least amount of bio-oil obtained was 33% ± 0.0085 from poplar branch at 550 °C. The highest amount of bio-oils from switchgrass (34% ± 0.023) was obtained at 450 °C. Water content in the bio-oil obtained from switchgrass was significantly higher than that from poplar. The GC–MS results showed that bio-oil compositions are similar among the various parts of poplar trees, with phenols being the dominant chemical specie and acids and alcohols present in negligible amounts. As temperature increases, an increase in furans is observed. Bio-oil and char fractions derived from stems have higher HHV than those from switchgrass, with the average HHV of char and water-free bio-oils ranging between 20.2 and 25.6 MJ/kg and 13.2 and −16.4 MJ/kg, respectively. Overall process energy recovery from initial biomass reached a maximum of 80.1% in the case of cottonwood main stem pyrolyzed at 500 °C.